Upaya Meningkatkan Keaktifan dan Hasil Belajar IPA Materi Bioteknologi dan Produksi Pangan Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share pada Siswa Kelas IX-8 MTsN 2 Kota Bima Tahun 2020/2021 - Siti Nuraini (Lembaga Bale Literasi, 2022)
This study aims to describe the activities of teachers and students in improving science learning outcomes material Biotechnology and Food Production for class IX-8 MTsN 2 Bima City by applying a Think Pair Share (TPS) cooperative model. This research is a Classroom Action Research (CAR). The subjects of this study were students of class IX-8 MTsN 2 Bima City totaling 32 students. This study was designed based on the Kemmis & Mc. Taggart. The stages of classroom action research developed are: planning, action, observation, and reflection. Data were collected using observation, assessment or test techniques, and documentation. Data analysis used qualitative descriptive analysis techniques that were sourced from data from observations of student activities and data from learning outcomes. The results of this study indicate (a) The application of the Think Pair Share method in learning science of biotechnology and food production is able to increase student activity. This is evidenced by the increase in learning activity from 18.75% or 6 students in the initial study to 43.75% or 14 students, and at the end of the second cycle to 96.88% or all students are active in learning; (b) The application of the Think Pair Share method in science learning of Biotechnology and Food Production is able to improve student learning outcomes. This is evidenced by the class average value continues to increase from 57.81 in the initial study to 62.50 in the first cycle, and at the end of the second cycle to 74.06, and is supported by an increase in learning mastery from 18.75% or 6 students in the initial study, became 14 students or 43.75% in the first cycle, and 96.88% in the second cycle or 31 students completed from the total number of students as many as 32 students